Brazilian government and the question of child labor: a sociohistorical study - Fernanda Kallyne Rêgo de Oliveira Morais; Maria de Nazaré de Oliveira Fraga (Rev Rene)
To analyze child labor is not an easy task due to the complexity of this question. This study aims: to analyze how children and adolescents have been treated historically; point out the advances in Brazilian Laws concerning this segment, focusing on the child labor. One analyzed historically the public policies on the light of the paradigms that supported them. We concluded that, nowadays, there are attitudes linked to different paradigms of the question’s approach, that there have been advances in the discourse area and that the theme child labor was inserted in Brazil’s public policies agenda, although in a weak way. Even though there are legal instruments, the Right Councils and Tutelary Councils must defi ne strategies that bring positive impacts for Brazilian children and adolescents who still work.